The Predominance of the Synthesis Phase in Cell Cycles in Childhood Acute Lymphoblastic Leukemia - Hernaningsih, Yetti; Aryati, Aryati; Ugrasena, I Dewa Gede; Nunki, Nastasya (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Uncontrolled proliferation and resistance to apoptosis should be controlled to kill the cancer cells, as the goal of treatment in acute leukemia. It is therefore important to know, which characteristic dominates the proliferative phase because, to be more effective, new drugs that will be developed should be targeted at that phase. This study aimed to find the dominant phase in the proliferative phase of the cell cycle in childhood Acute Lymphoblastic Leukemia (ALL). This study was conducted on 63 patients, comprising 33 patients with specimens of Bone Marrow Mononuclear Cells (BMMC), 30 patients with specimens of Peripheral Blood Mononuclear Cells (PBMC), and 10 children as controls with specimens of PBMC. Cell cycle examinations were performed with PI/RNase, run on BD FACS Calibur, and analyzed with modfit LT 4.1 software to determine the phases of G0/G1, synthesis (S), and mitosis (G2/M). Regarded the S and G2/M phases as the proliferation phase. Statistical analyses used one-way ANOVA and Kruskal-Wallis to compare S and G2/M phases within groups,and an Independent T-test and Mann-Whitney to compare the same phases between groups. Among the proliferation phases, the synthesis phase had significantly higher domination than the mitotic phase in both the BMMC (10.18±7.81% vs. 5.41±3.77%; p = 0.010) and PBMC (4.33±2.15% vs 2.30±1.56%; p=0.000) groups. A similar result was found in the control group (1.01±0.51% vs 0.36±0.38%; p=0.011). The synthesis phase in BMMC had significantly higher domination than PBMC groups (p=0.024) and control (p 0.002). The synthesis phase predominates among the proliferation phases of the cell cycle in childhood ALL.